1997
DOI: 10.1038/sj.bjp.0701528
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline, β‐adrenoceptor mediated vasorelaxation and nitric oxide in large and small pulmonary arteries of the rat

Abstract: 1 Noradrenaline induces a meagre vasoconstriction in small muscular pulmonary arteries compared to large conduit pulmonary arteries. We have examined whether this may be partially related to di erences in the b-adrenoceptor-mediated vasorelaxation component and, in particular, b-adrenoceptor-mediated NO release. 2 Noradrenaline induced a bell-shaped concentration-response in large (1202+27 mm) and small (334+12 mm) pulmonary arteries of the rat. In large arteries tension increased to 95.6+1.8% of 75 mM KCl (KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 25 publications
7
54
1
Order By: Relevance
“…We have previously demonstrated that isoprenaline concentrations above 100 nM cause a small but signi®cant aadrenoceptor-mediated vasoconstriction in pulmonary arteries of the rat (Priest et al, 1997). With the exception of experiments using PE or ME as the vasoconstrictor, all other studies involving isoprenaline were therefore performed in the presence of 10 mM phentolamine; we have previously shown that phentolamine has no e ect on salbutamol-induced relaxation (Priest et al, 1997). Tension was allowed to stabilize following every addition, and is expressed in terms of the initial induced tension.…”
Section: In¯uence Of Vasoconstrictor Type On Subsequent Relaxation Tomentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that isoprenaline concentrations above 100 nM cause a small but signi®cant aadrenoceptor-mediated vasoconstriction in pulmonary arteries of the rat (Priest et al, 1997). With the exception of experiments using PE or ME as the vasoconstrictor, all other studies involving isoprenaline were therefore performed in the presence of 10 mM phentolamine; we have previously shown that phentolamine has no e ect on salbutamol-induced relaxation (Priest et al, 1997). Tension was allowed to stabilize following every addition, and is expressed in terms of the initial induced tension.…”
Section: In¯uence Of Vasoconstrictor Type On Subsequent Relaxation Tomentioning
confidence: 99%
“…The presence of a functioning endothelium was determined by application of acetylcholine (ACh; 10 mM) following agonist induced contraction. After 60 min equilibration the arteries were subjected to a standard run up procedure of three 4 min exposures to PSS containing high K + (KPSS, 75 mM [K + ], equimolar substitution for NaCl) (Leach et al, 1992;Priest et al, 1997). Arteries producing less than 1 mN mm 71 were discarded.…”
Section: Tissue Preparationsmentioning
confidence: 99%
See 3 more Smart Citations